Answer:
x² + y² is equal to = (4 / 81)(845m² + 78m + 18)
Explanation:
We first need to get the values of x and y, which can be done using a system of equations, substituting one of the two functions into the other:
Given:
y = 2x + 2
3x + 3y = 26m
Then:
3x + 3(2x + 2) = 26m
3x + 6x + 6 = 26m
9x + 6 = 26m
9x = 26m - 6
x = (26m - 6) / 9
Now we can solve for y:
y = 2x + 2
y = 2(26m - 6) / 9 + 2
y = 2(26m - 6) / 9 + 18 / 9
y = (52m - 12 + 18) / 9
y = (52m + 6) / 9
Now we can sum up their squares:
x² + y²
= ((26m - 6) / 9)² + ((52m + 6) / 9)²
= (676m² - 312m + 36) / 81 + (2704m² + 624m + 36) / 81
= (3380m² + 312m + 72) / 81
= (4 / 81)(845m² + 78m + 18)